Comparing governance of international organisations: The EU, the OECD and educational policy - Kerstin Martens; Carolin Balzer; Reinhold Sackmann; Ansgar Wexmann (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2004)
How do international organisations (IOs) influence domestic policymaking? In the field of educational policy, IOs increasingly play an important role in shaping national debates and policies. Comparative studies as conducted by the OECD, for example, reveal strengths and weaknesses of individual educational systems and raise questions of "best practice". International initiatives such as the EU's Bologna Process even compel national policy makers to restructure their systems in such a way that students and staff will be able to move with more ease between systems and receive fair recognition of their qualifications in the near future. The aim of this study is to explore the forms of governance through which international organisations exercise influence on national policymaking. For this purpose, the EU and the OECD serve as case studies since these two organisations have recently been particularly active players in educational policy. Drawing on institutionalist approaches, an analytic grid will be designed in this study for systematically investigating the forms of governance as exercised by international organisations. The findings show that IOs have the most capacities to form and guide national policymaking through their distinctive ability to co-ordinate initiatives and to shape the ideas in a policy field, such as education.
Keywords: 370; Internationale Organisation; Bildungspolitik; Vergleich; EU-Staaten; OECD-Staaten; Governance-Ansatz